The Labor Market Integration of Immigrant Men and Women - Taryn Ann Galloway (Statistics Norway, Research Department, 2006)
Out of necessity, the earliest studies of immigrants' performance in the labor market in Western countries focused solely on men. However, as the employment rates of women in Western countries rise and approach those of men, questions about the labor market adjustments of immigrant women also become increasingly relevant. Furthermore, studies of earnings assimilation have typically analyzed only those individuals actually employed (full-time) in the labor market. Hence, they are unable to provide valuable insights into the extent to which the participation rates of immigrants - men or women - increase over time in the host country. This study analyzes explicitly the extent to which non-Western immigrants - both men and women - enter the labor market in Norway.
Keywords: J20; 330; Employment; Immigration; Integration; Assimilation